Role of LrrkA in the Control of Phagocytosis and Cell Motility in Dictyostelium discoideum - Bodinier, Romain; Sabra, Ayman; Leiba, Jade; Marchetti, Anna; Lamrabet, Otmane; Ayadi, Imen; Filić, Vedrana; Kawata, Takefumi; Weber, Igor; Cosson, Pierre (Frontiers in Cell and Developmental Biology, 2021)
LrrkA is a Dictyostelium discoideum kinase with leucine-rich repeats. LrrkA stimulates Kil2 and intra-phagosomal killing of ingested bacteria in response to folate. In this study we show that genetic inactivation of lrrkA also causes a previously unnoticed phenotype: lrrkA KO cells exhibit enhanced phagocytosis and cell motility compared to parental cells. This phenotype is cell autonomous, is reversible upon re-expression of LrrkA, and is not due to an abnormal response to inhibitory quorum-sensing factors secreted by D. discoideum in its medium. In addition, folate increases motility in parental D. discoideum cells, but not in lrrkA KO cells, suggesting that LrrkA plays a pivotal role in the cellular response to folate. On the contrary, lrrkA KO cells regulate gene transcription in response to folate in a manner indistinguishable from parental cells. Overall, based on analysis of mutant phenotypes, we identify gene products that participate in the control of intracellular killing, cell motility and gene transcription in response to folate. These observations reveal a mechanism by which D. discoideum encountering bacterially-secreted folate can migrate, engulf and kill bacteria more efficiently.